Do Director Elections Matter? - Fos, Vyacheslav; Li, Kai; Tsoutsoura, Margarita (Review of Financial Studies, 2018)
Using a hand-collected sample of election nominations for more than 30, 000 directors over the period 2001–2010, we construct a novel measure of director proximity to elections called Years-to-election. We find that the closer directors of a board are to their next elections, the higher CEO turnover-performance sensitivity is. A series of tests, including one that exploits variation in Years-to-election that comes from other boards, supports a causal interpretation. Further analyses show that other governance mechanisms do not drive the relation between board Years-to-election and CEO turnover-performance sensitivity. We conclude that director elections have important implications for corporate governance. Received March 10, 2016; editorial decision May 19, 2017 by Editor Itay Goldstein.